PENGEMBANGAN BUKU CERITA DIGITAL BERBASIS FLIPBOOK PADA MATERI ASAL-USUL UNTUK KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 1 SRIWIJAYA - Luthfiah, Naila; Fransyaigu, Ronald; Juliati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is the development of flipbook besed on a digital storybook media on original material for reading comprehension skills in fourth-students of grade four. This aims to validate, practicality, and effectiveness of flipbook- based digital storybook media. This study used a research and development approach based on the ADDIE model, which has five steps: analysis, design, development, implementation, and evaluation. Subjects of the study were fourth-grade students from SDN 1 Sriwijaya. The data collectiom to gather data included observations, interviews, question naires filled out by experts in media, materials, and language, survey about what teachers and students thought, and tests given before and after the study. The findings indicated that the media, expert validayion score reached 85.71%, categorized as “Very Appropriate” material experts were 89.00% categorized as “Very Appropriate”that and language experts were 88.88% categorized as “Very Appropriate”. At the implementation stage, the pratitioner’s assessment was 98.18% categorized as “Very Practical” and the student response was 91.52% categorized as “Very Practical”. The reial results showed that the N-Gain in the pretest and posttest results obtained value of 0.72% categorized as “Effective” which shows that the media is user-friendly in the learning process.